The Influence of Service Quality and Facilities on Purchase Intention at Bukit Asah Bali Camping Ground - Sari, Ni Komang Della Puspita; Witarsana, I Gusti Agung Gede; Suastini, Ni Made (PT FORMOSA CENDEKIA GLOBAL, 2024)
Service quality and facilities are important factors to increase purchase intention, so that with good service quality and facilities, it can influence the increase in purchase intention. This research was conducted at Bukit Asah Bali Camping Ground. This study aims to determine the effect of service quality and facilities on purchase intention at Bukit Asah Bali Camping Ground which was analyzed by SPSS. Data collection was carried out by distributing questionnaires and using a 5-point Likert scale. The analysis methods used are: classical hypothesis testing, multiple linear regression, t-test, F-test and coefficient of determination. The results of this study indicate that service quality and facilities partially have a positive and significant effect on purchase intention at Bukit Asah Bali Camping Ground and service quality and facilities simultaneously have a significant effect on purchase intention at Bukit Asah Bali Camping Ground. Service quality and facilities contribute to purchase intention by 49.9% which is obtained through the analysis of the coefficient of determination, while the remaining 50.1% is the influence of other variables not examined in this study.